Odobenus rosmarus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Odobenus rosmarus (Linnaeus 1758) [Phoca] rosmarus Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 38. Type Locality: "intra Zonam arcticam Europae, Asiae, Americae". Vernacular Names: Walrus. Subspecies:: Subspecies Odobenus rosmarus subsp. rosmarus Linnaeus 1758 Subspecies Odobenus rosmarus subsp. divergens Illiger 1815 Subspecies Odobenus rosmarus subsp. laptevi Chapskii 1940 Distribution: Arctic sea- coastal regions of Belgium (vagrant), Canada, Great Britain (vagrant), Greenland, Iceland (vagrant), Japan (Honshu), Netherlands (vagrant), Norway, Russia, USA (Alaska, New England-vagrant). Conservation: CITES – Appendix III (Canada); IUCN – Data Deficient as O. r. laptevi , otherwise Lower Risk (lc). Discussion: Reviewed by Fay (1985). Synonyms allocated according to Ellerman and Morrison-Scott (1951) and Fay (1985). Distributional information from Rice (1998). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 594, DOI: 10.5281/zenodo.7316519